Identifying Public Awareness and Implementation Challenges in 3R-Based Household Waste Management: A Case Study of Kendari City, Southeast Sulawesi - Selviani Novita Dompasa; Dwiprayogo Wibowo; Sumarlin Sumarlin (Lembaga Penelitian, Universitas Warmadewa, 2026)
Household waste management is an increasingly complex environmental issue in line with population growth and rising community activities. This study aims to examine household waste management practices based on the 3R principles (Reduce, Reuse, Recycle) in Kambu Urban Village (Kendari, City, Southeast Sulawesi) and to analyze the level of public awareness and the constraints encountered in its implementation. A mixed-methods approach was employed, using questionnaires, interviews, and observations for data collection. Respondents were selected through random sampling from the local community. The results indicate that household waste management based on the 3R principles is perceived as very poor, with a mean score of 4.43. The availability of 3R facilities and infrastructure is also categorized as very inadequate, with a mean score of 4.39. Community participation and support remain very low, reflected by a mean score of 4.27. However, respondents demonstrated relatively good awareness of the environmental benefits of implementing the 3R concept, with a mean score of 4.31. The main constraints in optimizing 3R-based waste management include limited availability of waste segregation bins, absence of waste banks, and inadequate waste collection services in narrow residential alleys. This study reveals that household-level 3R waste management in Kambu Village has not been optimally implemented due to infrastructural limitations and low community engagement.